2006
DOI: 10.1007/s00535-006-1909-8
|View full text |Cite
|
Sign up to set email alerts
|

A deficiency of gastric interstitial cells of Cajal accompanied by decreased expression of neuronal nitric oxide synthase and substance P in patients with type 2 diabetes mellitus

Abstract: These results suggest that lower gastric ICC, nNOS, and SP densities in patients with DM may be associated with the pathogenesis of diabetic gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
157
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 44 publications
16
157
3
Order By: Relevance
“…The cytoplasm was partially dissolved, there were fewer organelles and a number of autophagic vacuoles could be observed within the cytoplasm. The reduction in the number of organelles within the ICCs was consistent with the literature (3,4,7,17).In addition, the peripheral axons and dendrites were partially swollen or dissolved, the electron density was not uniform, and vacuoles had formed. The synaptic vesicle content inside the nerve varicosity was significantly reduced, and the number of gastric ICCs was significantly decreased compared with the blank group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cytoplasm was partially dissolved, there were fewer organelles and a number of autophagic vacuoles could be observed within the cytoplasm. The reduction in the number of organelles within the ICCs was consistent with the literature (3,4,7,17).In addition, the peripheral axons and dendrites were partially swollen or dissolved, the electron density was not uniform, and vacuoles had formed. The synaptic vesicle content inside the nerve varicosity was significantly reduced, and the number of gastric ICCs was significantly decreased compared with the blank group.…”
Section: Discussionsupporting
confidence: 90%
“…Between 30 and 50% of patients that have had diabetes for >10 years exhibit such symptoms of gastric neuromuscular dysfunction as satiety, weight loss, abdominal pain, distension and discomfort, nausea and vomiting. Neuropathological changes, a reduction in the number of gastrointestinal interstitial cells of Cajal (ICCs), morphological changes, hyperglycemia, microvascular diseases, microcirculatory disorders, gastrointestinal hormone changes and Helicobacter pylori are all believed to be involved in the pathogenesis of diabetic gastroparesis (DGP) (1)(2)(3)(4)(5)(6)(7). The inherent gastric nerves have recently been subject to significant focus, and it has been suggested that the most important mechanism of DGP is the deficiency of neuronal nitric oxide synthase expression and the reduction of ICCs (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ICC, which is known to regulate spontaneous contraction by generating slow waves in the smooth muscle of the gastrointestinal tract, has been increasingly studied. 17,[26][27][28][29][30][31][32][33][34][35][36] Many studies have reported that ICC injury plays an important role in various chronic diseases that cause abnormal gastrointestinal contractions. 27,[29][30][31][32][33]35 In addition, it has been reported that spontaneous contraction signals are transmitted by ICC networks and that the loss of small intestinal motility in humans was caused by reduction in the ICC networks.…”
Section: Discussionmentioning
confidence: 99%
“…A relative loss of ICC in colonic surgical specimens from children with congenital aganglionosis of Hirschsprung's disease was reported 29,31 . Decreased populations of ICC were observed in chronic idiopathic intestinal pseudoobstruction 15,26 , slow-transit constipation 12,13,20,29,30 , and also in diabetic gastroenteropathy 13,16 . Hagger et al 11 , Geraldino et al 8 , and Iantorno et al 14 have demonstrated a reduction of ICC in the resected colon or in colonic biopsies in Chagasic patients with megacolon compared to the colon of non-Chagasic patients.…”
Section: Discussionmentioning
confidence: 98%